Education as Function of Productivity: An Hermeneutic Study of Standards on Ethics and Integrity in Human Resource Development Texts - Vicki K. Carter; Sharon L. Howell; Fred M. Schied (Adult Education Research Conference, 2001)
This critical hermeneutic analysis of the AHRD Standards on Ethics and Integrity and six HRD textbooks identifies unexamined assumptions and silences related to the practice of HRD.